Enterprise Resource Planning Based Open Source - Pamungkas, Canggih Ajika; Iskandar, Dwi (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2021)
In the era of the 4.0 industrial revolution, companies are trying to implement information technology to increase competitive competitiveness. Information technology is implemented within the company to increase productivity and help achieve quality, time standards, and satisfaction for consumers and employees, wherein business this is manifested in a set of systems consisting of information systems and supporting infrastructure. One solution is to implement a system to manage all company resources or what is called an Enterprise Resource Planning (ERP) system. Implementing an ERP system requires high costs and is highly dependent on the vendor. The purpose of this research is to build an ERP system on an open-source basis so that it can be used by middle to lower enterprises as an alternative to ERP systems to support the company's operations.The ERP system was developed using the waterfall system development method. The result of this research is the development of an ERP system based on open source. The conclusion of this research is that the ERP system can be configured according to the needs of small and medium scale companies. Can record documentation of company operational activities. The centralized database system provides benefits for companies to view data on business operations. Suggestions given for further research are to develop warehouse management and material management modules.